Establishing the First Mobile Stroke Unit in the United States. Issue 5 (May 2015) - Parker, Stephanie A.; Bowry, Ritvij; Wu, Tzu-Ching; Noser, Elizabeth A.; Jackson, Kamilah; Richardson, Laura; Persse, David; Grotta, James C.
Abstract : Background and Purpose—: Recently, the Mobile Stroke Unit (MSU) concept was introduced in Germany demonstrating prehospital treatment of more patients within the first hour of symptom onset. However, the details and complexities of establishing such a program in the United States are unknown. We describe the steps involved in setting up the first MSU in the United States. Methods—: Implementation included establishing leadership, fund-raising, purchase and build-out, knitting a collaborative consortium of community stakeholders, writing protocols to ensure accountability, radiation safety, purchasing supplies, licensing, insurance, establishing a base station, developing a communication plan with city Emergency Medical Services, Emergency Medical Service training, staffing, and designing a research protocol. Results—: The MSU was introduced after ≈1 year of preparation. Major obstacles to establishing the MSU were primarily obtaining funding, licensure, documenting radiation safety protocols, and establishing a smooth communication system with Emergency Medical Services. During an 8 week run-in phase, ≈2 patients were treated with recombinant tissue-type plasminogen activator per week, one-third within 60 minutes of symptom onset, with no complications. A randomized study to determine clinical outcomes, telemedicine reliability and accuracy, and cost effectiveness was formulated and has begun. Conclusion—: The first MSU in the United States has been introduced in Houston, TX. The steps needed to accomplish this are described. Abstract : Supplemental Digital Content is available in the text.